2001
DOI: 10.1046/j.1440-1819.2001.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Nineteen‐hour variation of postural sway, alertness and rectal temperature during sleep deprivation

Abstract: Nineteen-hour variation of postural sway, alertness and rectal temperature during sleep deprivation were studied. Alertness decreased gradually at night and remained low until morning. Postural sway in the eyes-closed condition increased during early morning. In six of the eight subjects the greatest sway was observed during the 3-h period when rectal temperature was at its minimum. It is suggested that unbearable sleepiness during sleep deprivation will give rise to measurable impairment of postural balance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
76
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 2 publications
19
76
2
Order By: Relevance
“…The AAT method is excellent, because it differs from the conventional MSLT which is needed various experiment conditions and the point that objective wakefulness level can be presumed in a short time and by easy technique. Moreover it is suggested that AAT is based on the physiological phenomenon in which if sleepiness increases alpha wave decrease in closed eyes condition and increases in opened eyes condition, and also AAT have high sensitivity to the degree of awakening [18][19][20][21] . Therefore, AAT method would be suitable as an index which measures an wakefulness level by whole-body vibration exposure in a short-period, because it can measure in a short time and there is little pain to a subjections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AAT method is excellent, because it differs from the conventional MSLT which is needed various experiment conditions and the point that objective wakefulness level can be presumed in a short time and by easy technique. Moreover it is suggested that AAT is based on the physiological phenomenon in which if sleepiness increases alpha wave decrease in closed eyes condition and increases in opened eyes condition, and also AAT have high sensitivity to the degree of awakening [18][19][20][21] . Therefore, AAT method would be suitable as an index which measures an wakefulness level by whole-body vibration exposure in a short-period, because it can measure in a short time and there is little pain to a subjections.…”
Section: Discussionmentioning
confidence: 99%
“…EEG was measured using an electroencephalograph (Nihon Kohden; Neuropack Four, Japan), and after FFT treatment (1 section 4-s, 100 Hz of sampling frequencies) using the [18][19][20][21][22][23] . When the power spectrum of alpha-wave becoming large during closed eyes, if a wakefulness level is high, blocking becomes remarkable during opened eyes and the power spectrum of alpha-wave decreases sharply.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency analysis of tremor intensity was conducted with the fast Fourier transform method. These functions did not seem to be affected by a diurnal variation because no special conditions such as sleep deprivation or night work existed [14][15][16] . Also, postural sway in children tends to be larger in boys than in girls, but tremor does not differ according to sex 17) .…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Mental fatigue can be subjectively assessed. It has, however, been shown that such an evaluation does not fully reflect the objective, physiological status of a tired person, mainly because subjective reports are biased by motivation, personal factors, experience and training.…”
Section: J Ma Y-j Yao R-m Ma Et Almentioning
confidence: 99%
“…In this context, the objective, computerized assessment of postural control, known to be intimately linked with neurophysiological processes affected by fatigue, appears to be a promising method of fatigue assessment. 3,4,11 It has been shown that postural stability and motor control are affected by > 19, 24 or 48 h of sleep deprivation, 4,9,12 -14 although the mechanism by which sleep deprivation exerts these effects has yet to be determined. The effect of sleep deprivation on postural sway is correlated with reduced levels of alertness, 9 peaking when the body temperature reaches its minimum.…”
Section: J Ma Y-j Yao R-m Ma Et Almentioning
confidence: 99%